2019
DOI: 10.1039/c9dt03363g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and electropolymerization of N-heterocyclic carbene complexes of Pd(ii) and Pt(ii) from an emissive imidazolium salt with a terthiophene backbone

Abstract: The synthesis of an emissive terthiophene-based imidazolium iodide as the corresponding N-heterocyclic carbene (NHC) preligand (4), and its Pd and Pt–NHC complexes (5a, 5b), along with their electropolymerized electrochromic polymers (P1–3) are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Commonly, nitro groups are introduced in positions 3 and 4 of 2,5-dibromothiophene. The resulting 2,5-dibromo-3,4-dinitrothiophene is coupled with organotin or organoboron thiophene derivatives in a metal-catalyzed Stille or Suzuki reaction, thus affording 3′,4′-dinitro trimers [ 27 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 ]. In some cases, the organotin or organoboron thiophene derivatives carried alkyl or ether chains, that were in this way introduced on the resulting dinitroterthiophene [ 101 , 180 , 181 , 182 , 183 , 184 , 185 , 186 , 187 , 188 , 189 , 190 ].…”
Section: Trimer Structuresmentioning
confidence: 99%
See 3 more Smart Citations
“…Commonly, nitro groups are introduced in positions 3 and 4 of 2,5-dibromothiophene. The resulting 2,5-dibromo-3,4-dinitrothiophene is coupled with organotin or organoboron thiophene derivatives in a metal-catalyzed Stille or Suzuki reaction, thus affording 3′,4′-dinitro trimers [ 27 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 ]. In some cases, the organotin or organoboron thiophene derivatives carried alkyl or ether chains, that were in this way introduced on the resulting dinitroterthiophene [ 101 , 180 , 181 , 182 , 183 , 184 , 185 , 186 , 187 , 188 , 189 , 190 ].…”
Section: Trimer Structuresmentioning
confidence: 99%
“…For this reason, nitro groups are sometimes reduced after the formation of the trimer. In this case, iron metal in acetic acid solvent has been used as an alternative to SnCl 2 /HCl for the nitro reduction [ 165 , 171 ]. Other reduction methods involve H 2 on Ni in ethanol [ 185 ], H 2 on Pd/C in ethyl acetate [ 201 ] or Zn metal in acetic acid [ 184 ].…”
Section: Trimer Structuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, 2-aryl-4,6-di(2-thienyl)thieno[3,4-b]imidazole derivatives ( 3 ) have been studied as the electron donor species in dye-sensitized solar cells [ 18 ]. As part of a wider study of terthiophene-based imidazole molecules, we recently reported the preparation of 4,6-di(2-thienyl)thieno[3,4-b]imidazole ( 4 , DTTI) [ 19 ] ( Scheme 1 ). An easily prepared derivative of 4 is the dicarboxylic acid derivative, 5,5′-1 H -thieno[3,4-d]imidazole-4,6-diyl) bis (thiophene-2-carboxylic acid) ( 5 , TIBTCH 2 ); here, we present an investigation of its efficacy in the construction of new emissive MOFs.…”
Section: Introductionmentioning
confidence: 99%